(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Gridhrasi comes under 80 types of Nanatmaja (different) Vatavyadhis (disorders due to Vata) and frequently encountered in clinical practice. In this condition the patient become incapable to do his daily routine works because of severe pain from Kati Pradesa (Lumbar region) to Padanguli (foot). No definite choice of treatment available in modern medicine except symptomatic treatment and surgery. The present study was designed to study Vrishadi Vasti in Gridhrasi in Yoga vasti protocol, comprising 3 days Kashaya Vasti (Nirooha) with Vrishadi Vasti and 5 days Anuvasana Vasti with Sahacharadi Tailam Chikkana Pakam. A total of 30 patients in the age group of 20-70 years of either sex were selected for the study. Before commencing Yogavasti, all patients were subjected to Rooksha Sweda with Kolakulathadi Choorna, Gandharvahastadi Kashaya and Vaiswanara Choorna for Deepana and Pachana followed by Patrapotali Sweda. The demographic data and data related to cardinal symptoms of Gridhrasi were analysed by using the most appropriate statistical tests. The patients were assessed before treatment, after treatment, and after 15 & 30 days of follow up period. Vrishadi Vasti along with other Agnideepana, Anulomana drugs, Rooksha Sweda and Patrapotali Sweda was found to be significantly effective in reducing the signs and symptoms of Gridhrasi like Ruk, Toda, Stambha and Gourava. After treatment there was marked improvement in straight leg rising, but it was found to be statistically insignificant in twitching (Spandana). There was marked improvement in all patients after the second follow up, shows the long term effect of Vasti.